Conflict and compromise over processional sound in 19th-century Singapore. Issue 133 (2nd September 2017) - McCallum, Jenny
ABSTRACT: This article traces conflicts and compromises over sounds associated with processions in colonial Singapore from the first recorded conflict in 1837 until tensions on this topic subsided in the late 1870s. Following the establishment of a British settlement there in 1819, Singapore became a meeting place for migrant communities of diverse cultural backgrounds as large numbers of workers arrived in the flourishing port. One of the stages on which intercommunal power dynamics were played out was the conflict over the right to make sound at particular times and places. Conflict over 'noise' ostensibly originated in the encounter between communities with fundamentally different sonic ideologies. British colonial authorities sought to control Asian sounds, while their colonial subjects resisted their attempts. If British principles of regulation had been enforceable, the conflict over processions would have been short-lived. In practice, the duration and complexity of the clashes demonstrates that the British were not decisively in control on this issue. Rather, a high level of compromise and negotiation between various ethnic communities was involved alongside simple colonial domination and resistance, frequently involving multilateral negotiations between Singapore's Asian communities and comparisons with governmental policy elsewhere. The vigorous efforts of Singapore's Asian inhabitants to defend their sounding traditions, and of the colonial authorities' attempts to control them, demonstrate the significance and usefulness of sound in the context of this divided colonial city.